SOCIOSCIENTIFIC ISSUES (SSI) IN REACTION RATES TOPIC AND ITS EFFECT ON THE CRITICAL THINKING SKILLS OF HIGH SCHOOL STUDENTS - Pratiwi, Y. N.; Rahayu, S.; Fajaroh, F. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2016)
The aim of this research was to investigate the difference in students’ critical thinking which learnt cooperatively using different learning context. Quasy experimental postest only control group design was chosen as experimental design using two equivalent classes as the sample. The first class (15 MIA 5, n = 30) was taught using socioscientific issues (SSI) as the learning context and the second one (15 MIA 6, n = 30) was not. The research instrument was a test consisted of 16 items of multiple choice questionsdeveloped based on Ennis’ critical thinking indicators. This instrument have been validated and its reliability approved with r = 0,765. Students’ post-test scores were analyzed using t-test with SPSS 16 for Windows. The result showed that statistically students’ critical thinking skills betweentwo classes was significanly different (Asym. Sig = 0,037). Students who taught using SSI have higher score (73,96) than the one wasn’t (66,04). Result shows that using socioscientific issues (SSI) as learning context has significant effect on high school students’ critical thinking skills.